Joint Channel Allocation and Power Control for Mission-Critical Applications in Sustainable Underwater Acoustic Networks - Sadaf Vahabli; Iftekhar Ahmad; Quoc Viet Phung; Daryoush Habibi (IEEE Access, 2025)
Underwater Acoustic Networks (UANs) are gaining popularity for underwater communication due to their long-range capabilities. However, they experience significant challenges, including limited bandwidth and spectrum overlap with marine mammal vocalizations, which raises concerns about the sustainable and ethical use of underwater acoustic resources. This study proposes an eco-friendly approach that integrates joint channel allocation and power control to minimize harmful interference with marine life while ensuring reliable communication for mission-critical applications, such as diver safety. To balance marine protection and communication reliability, this work introduces a strategy for intelligent spectrum management, where nodes first sense the acoustic spectrum to detect the presence of marine mammals, followed by channel gain calculations. Based on these insights, a spectrum decision mechanism allocates appropriate channels, and the power control mechanism determines optimal transmission power levels that minimize interference with marine mammals. The model also guarantees the minimum required transmitter power for critical applications, thereby avoiding network disconnections and ensuring the required Quality of Service (QoS) rate. Results show that the proposed solution achieves a practical trade-off by improving total network capacity and reducing end-to-end delay, while minimizing environmental impact and lowering computation complexity compared to related studies. This work promotes the environmental sustainability of underwater acoustic networks, aligning with the UN Sustainable Development Goals.